2023
DOI: 10.3390/molecules28083332
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties, Antioxidant Markers, and Meat Quality as Affected by Heat Stress: A Review

Abstract: Heat stress is one of the most stressful events in livestock life, negatively impacting animal health, productivity, and product quality. Moreover, the negative impact of heat stress on animal product quality has recently attracted increasing public awareness and concern. The purpose of this review is to discuss the effects of heat stress on the quality and the physicochemical component of meat in ruminants, pigs, rabbits, and poultry. Based on PRISMA guidelines, research articles were identified, screened, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 134 publications
(190 reference statements)
0
5
0
Order By: Relevance
“…As is known, HS has multiple adverse impacts on rabbits’ health statuses and their production performance. It has been revealed that HS is responsible for a 9–12% increase in mortality rate, 20–25% reductions in average daily weight gain, and 8–15% decreases in feed conversion ratio, as well as negatively affecting the carcass traits and quality of meat in growing rabbits [ 3 , 4 ]. Thus, HS poses a significant challenge for the rabbit industry, made worse by recent global warming [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is known, HS has multiple adverse impacts on rabbits’ health statuses and their production performance. It has been revealed that HS is responsible for a 9–12% increase in mortality rate, 20–25% reductions in average daily weight gain, and 8–15% decreases in feed conversion ratio, as well as negatively affecting the carcass traits and quality of meat in growing rabbits [ 3 , 4 ]. Thus, HS poses a significant challenge for the rabbit industry, made worse by recent global warming [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HS poses a significant challenge for the rabbit industry, made worse by recent global warming [ 1 ]. Several previous studies have investigated prospective mitigation strategies, and nutritional manipulation has proven to be a dynamic mitigation approach [ 4 , 5 ]. The dietary supplementation of animal diets with herbs or spices and their derivatives has provided appropriate evidence as a potential alternative to antibiotics for alleviating the negative effects of HS during summer.…”
Section: Introductionmentioning
confidence: 99%
“…Meat quality is influenced not only by genetic factors but also by environmental factors such as temperature, humidity, light, and harmful gas content. The indicators for evaluating meat quality include pH, meat color (a*, b*, and L* values), shear force, dripping loss, cooking loss, fat, ash and protein ( 17 , 23 , 42 , 43 ). Currently, research results on the cooking loss of Pekin ducks under different temperatures are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Maintaining redox balance is essential for effective immunity and health. Therefore, the determination of antioxidant indices may reflect the pattern of free radical metabolic changes in vivo ( 15 , 23 , 48–50 ). There are differences in the sensitivity of various antioxidant indicators in the serum of experimental ducks to temperature treatments.…”
Section: Discussionmentioning
confidence: 99%
“…LC-MS, as one of the assays to detect metabolites, is able to provide a comprehensive coverage of substances and is considered to be a suitable technique for studying metabolism [50]. Numerous studies have documented that HS reduced meat quality by altering energy metabolism, amino acid transport, glycolysis, intramuscular fat deposition, and protein synthesis [36,[51][52][53]. In our study, a total of 312 metabolites were identified based on metabolomics analysis, mainly including organic acids, sugars, and amino acids, which were enriched in amino acid and organic acid metabolism using the KEGG analysis.…”
Section: Discussionmentioning
confidence: 99%